2(13t-15)+3(t-19)=0

Simple and best practice solution for 2(13t-15)+3(t-19)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(13t-15)+3(t-19)=0 equation:


2(13t-15)+3(t-19)=0

We simplify the equation to the form, which is simple to understand
2(13t-15)+3(t-19)=0

Reorder the terms in parentheses
+(+26t-30)+3*(t-19)=0

Remove unnecessary parentheses
+26t-30+3+*(+t-19+)=0

Reorder the terms in parentheses
+26t-30+(+3t-57)=0

Remove unnecessary parentheses
+26t-30+3t-57=0

We move all terms containing t to the left and all other terms to the right.
+26t+3t=0+30+57

We simplify left and right side of the equation.
+29t=+87

We divide both sides of the equation by 29 to get t.
t=3

See similar equations:

| 4x-10+2x=3(5x-5)+2 | | x=-9x^2+x+10 | | -2(2+x)=7(-3x-1) | | -25+10c^2=c^2 | | 3x+2.6=x+24 | | 5+6(-1)= | | 2h^2-7h-1= | | 15x-6.3=0 | | g^2+3g= | | 4t^2+8t= | | -7(x-1)=-4(x+7) | | -2x+7=9x+3 | | 5+6z= | | x/5=17 | | .25(y-b)=m | | 3t+5=-15 | | 5-2x=3+3x-4x | | 8x+10-(2x+5)=-55 | | -2(m-60)=-m | | 5m=3m+6 | | 9x=2x^2-18 | | 8x-12=15x+10 | | 6x+12=-6 | | 4+p^2+12p=0 | | 2(x-3)=x+9 | | X^2+7x-38=0 | | x^2+50x+336=0 | | 4x+12=-2(x-3) | | -3(2x-1)=4-3x | | x^2-8x-1008=0 | | s-31=20.6 | | 6x+2=8x-2 |

Equations solver categories